WACANA BAHASA INGGRIS BERDASARKAN KETERAMPILAN BERBAHASA KELAS X MAN 2 PAREPARE - H. Ambo Dalle (Al-Ishlah: Jurnal Pendidikan Islam, 2015)
This study aims to discuss the teaching skills of listening, speaking, reading and writing of X MAN 2 Parepare; and the discourse mastery of English through listening, speaking, reading and writing. The results showed that the teaching of language skills listening, speaking, reading, and writing of X MAN 2 Parepare is not adequate because the implementation did not get level of 66.67%. Inadequate implementation of the teaching of language skills in this regard due to the application of learning, teaching materials management, and utilization of the facilities or infrastructure associated with teaching and learning process is not optimal. English discourse mastery based on the teaching of language skills of X MAN 2 Parepare is considered inadequate or did not get 75% of students who got score more than 7 on all four of the discourse mastery process. Thus, students have not mastered the English language discourse by teaching language skills.